The Concepts of Khouf and Roja' in The Qur'an as The Spiritual Foundation of Islam for The Practice of Mindfulness - Fitriyyah, Lina Ayu (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2025)
This study aims to examine the concepts of khouf and roja' thematically in the Qur'an, including their interpretation by exegetes, and to analyze the function of these two concepts as a spiritual basis for achieving emotional balance and peace of mind. In addition, this study also explains the relevance and application of khouf and roja' in the practice of mindfulness from an Islamic perspective, as a strategy for overcoming psychological and spiritual crises in the present day. Thus, this study is expected to contribute theoretically to the study of the Qur'an and Sufism, as well as practically to the development of mental health methods based on Islamic values. This study uses a qualitative method with library research. Data was collected through documentation techniques on verses from the Qur'an, tafsir books, and contemporary Sufism and psychology literature, then analyzed using a maudhū‘ī (thematic) interpretation approach. The results of the study show that khouf functions as moral awareness that fosters caution, self-control, and spiritual discipline, while roja' acts as a source of optimism, inner peace, and psychological resilience. The integration of the two forms an emotional and spiritual balance that is an important foundation in the Islamic perspective of mindfulness. Thus, Qur'anic mindfulness is not only oriented towards emotional regulation, but also towards strengthening faith and character building. This study concludes that the concepts of khouf and roja' are relevant to be developed as a holistic Islamic mindfulness model, which combines psychological well being and spiritual depth in facing modern life crises.